Electronic signatures law and regulation - Brazell, Lorna (Sweet & Maxwell LondonGB, 2004)
Provides a comparative approach to the topic of electronic signatures by covering 54 countries and territories. Illuminates the legislation in the context of differing approaches to signatures.